Differences in EEG Oscillations during Vasoactive Stress Reactions in Extroverts and Introverts - Kustubayeva, A.M.; Matthews, G. (Vestnik Rossiĭskogo universiteta druzhby narodov. Serii͡a︡ psikhologii͡a︡ i pedagogika, 2012)
Hyperventilation (HV) and breath-holding (BH) are informative psychophysiological tests resulting in rapidly changing cerebral blood flow. The aim of our research was to determine differential EEG spectra of introverts/extroverts with induced HV and BH. Introverts revealed more intensive EEG reaction during HV, which was specifically shown by increased theta and gamma activity in all cortical areas.